Familial aggregation of leisure-time physical activity across three generations: The Cardiovascular Risk in Young Finns Study - Yang, Xiaolin; Kukko, Tuomas; Rovio, Suvi P.; Pahkala, Katja; Salin, Kasper; Hutri-Kähönen, Nina; Raitakari, Olli T.; Tammelin, Tuija H. (SAGE Publications, 2026)
Aims:
Leisure-time physical activity (LTPA) is known to be hereditary for two generations, but its transmission beyond that is less studied. This study examined LTPA aggregation in three-generation families.
Methods:
Data on self-reported LTPA were extracted from the Young Finns Study in 2018–2020, including three generational groups: offspring (G2; aged 7–38 years, n = 2499), parents (G1; aged 43–58 years, n = 1960) and grandparents (G0; aged 58–94 years, n = 2190). In the analysis, G2 was categorized into two age groups: youth offspring (aged 7–18 years) and adult offspring (aged 19–38 years). Correlations, chi-square test and binary logistic regressions were used to compare the differences in LTPA levels (low vs. high) between G1–G2, G0–G2 and G0–G1, stratified by gender and age.
Results:
In the youth offspring group, high-active G1 fathers were more likely to have highly active G2 sons, while high-active G1 mothers were more likely to have highly active G2 daughters when compared with their low-active counterparts. High-active G0 maternal grandmothers had a higher probability of having highly active G2 granddaughters than low-active maternal grandmothers. In the adult offspring group, high-active G0 maternal grandfathers were more likely to have highly active G2 grandsons compared with low-active maternal grandfathers.
Conclusions:
The study highlights the role of familial modelling in shaping LTPA behaviours, especially in younger generations. The findings support targeted, family-based interventions to promote LTPA early in life, considering gender- and age-specific dynamics.